Tissue damage between barbed suture and conventional sutures in animal laboratory model using scanning electron microscopy - Tomomi Shiga; Hideshi Okada; Masanori Isobe; Tatsuro Furui (Journal of Obstetrics and Gynaecology)
This study aimed to compare the tissue damage caused by barbed sutures and conventional sutures using scanning electron microscopy (SEM). Porcine myocardium was incised and sutured using different thread types: barbed suture, (STRATAFIX® Spiral PDS PLUS) and conventional sutures, (VICRYL® and PDS Plus®). Needle hole shapes were examined at magnifications of 30×–100×. VICRYL® suture damaged the tissue and created large gaps around the needle holes. The tissue around the needle holes was smoother and less damaged in the single suture ligations with PDS®; however, a large gap had formed. In the continuous suture with STRATAFIX®, the tissue around the needle holes was significantly smoother and minimally damaged, with no noticeable gaps around the needle holes. Barbed sutures reduced the load on needle holes and minimised tissue damage owing to the dispersion of traction forces by the barbs compared with conventional sutures.